Introduction of 2-O-benzyl abasic nucleosides to the 3′-overhang regions of siRNAs greatly improves nuclease resistance. Issue 24 (15th December 2017) - Nagaya, Yuki; Kitamura, Yoshiaki; Shibata, Aya; Ikeda, Masato; Akao, Yukihiro; Kitade, Yukio
Graphical abstract: Abstract: Chemically modified siRNAs containing 2- O -benzyl-1-deoxy-d -ribofuranose (R H OBn ) in their 3′-overhang region were significantly more resistant towards serum nucleases than siRNAs possessing the natural nucleoside in this region. The knockdown efficacies and binding affinities of these modified siRNAs to the recombinant human Argonaute protein 2 (hAgo2) PAZ domain were comparable with that of siRNA with a thymidine dimer at the 3′-end.